Pandemi Covid-19: Pengaruh Perilaku Konsumtif dan Mental Accounting Terhadap Pengelolaan Keuangan Mahasiswa FKIP UKSW - Indah Lely Cristanti; Dwi Iga Luhsasi; Destri Sambara Sitorus (Jurnal Akuntansi dan Pajak, 2021)
This study aims to have a direct impact on consumer behavior and mental accounting on financial management either partial or simultaneously. The population recruited in this study were SWCU FKIP students adding 1.291 from various study programs. The sampling technique used was cluster sampling where the data source was too broad and the sampling was based on the population area, the sample used 298 SWCU FKIP students used the Isaac and Michael's formula. Collecting data through distributing questionnaires online with a Likert Scale. The questionnaire test used test in the form of normality test, multicollinearity test, heteroscedasticity test and linearity test as well as additional validity and reliability tests. The classical assumption test that is carried out does not occur problems and can be proposed. The statistical methods used is multiple linear regression with a significant level of 5%. The redults of this study indicate that there is no significant influence between consumptive behavior and financial management 0.112 > 0.05, and there is a significant influence between mental accounting on financial management of 0.000 < 0.05. simultaneously, there is a significant influence between consumptive behavior and mental accounting on financial management of 0,000 < 0.05 has a significant impact. Keywords: Consumptive Behavior, Mental Accounting, Financial Management